Al-Khawarizmi Serta Kontribusinya Untuk Perkembangan Sains Modern - Rahmanita, Fatia; Nashihah, Durrotun; Ramadhan, Muhammad Fadli (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
The current development of science is the result of the knowledge development carried out by previous scientists, including Al-Khwarizmi. One of the Muslim scientists who lived during the Abbasid era. He is a leading Muslim scientist who made many contributions to human civilization. As a great figure of his time, Al-Khwarizmi produced many monumental works. This article discusses Al-Khwarizmi's biography and his contribution to the development of science in the modern era. To obtain this information, researchers conducted a literature review related to the topic. The results of the literature review show that Al-Khwarizmi made many contributions and thoughts in the fields of mathematics and astronomy which are very helpful for the benefit and development of science in the modern era.